2023
DOI: 10.3390/ijms24076406
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cannabinoid Receptor 2 (CB2) Low Lipophilicity Agonists Produce Distinct cAMP and Arrestin Signalling Kinetics without Bias

Abstract: Cannabinoid Receptor 2 (CB2) is a promising target for treating inflammatory diseases. We designed derivatives of 3-carbamoyl-2-pyridone and 1,8-naphthyridin-2(1H)-one-3-carboxamide CB2-selective agonists with reduced lipophilicity. The new compounds were measured for their affinity (radioligand binding) and ability to elicit cyclic adenosine monophosphate (cAMP) signalling and β-arrestin-2 translocation with temporal resolution (BRET-based biosensors). For the 3-carbamoyl-2-pyridone derivatives, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Agonist stimulation of CB 2 receptors canonically activates Gα i/oβγ heterotrimers leading to inhibition of adenylate cyclase with consequent reduced cAMP production, activation of signalling pathways such as MAPKs, and recruitment of β-arrestin which facilitates desensitisation, internalisation and potentially further signal transduction (Oyagawa & Grimsey, 2021). Coupling to Gα q and Gα s have also been reported, as well as biased agonism and temporal signalling signatures, which are hypothesised to influence responses downstream of CB 2 receptor activation (Oyagawa & Grimsey, 2021;Sharma et al, 2023).…”
Section: Cb Expression and Functionmentioning
confidence: 99%
“…Agonist stimulation of CB 2 receptors canonically activates Gα i/oβγ heterotrimers leading to inhibition of adenylate cyclase with consequent reduced cAMP production, activation of signalling pathways such as MAPKs, and recruitment of β-arrestin which facilitates desensitisation, internalisation and potentially further signal transduction (Oyagawa & Grimsey, 2021). Coupling to Gα q and Gα s have also been reported, as well as biased agonism and temporal signalling signatures, which are hypothesised to influence responses downstream of CB 2 receptor activation (Oyagawa & Grimsey, 2021;Sharma et al, 2023).…”
Section: Cb Expression and Functionmentioning
confidence: 99%
“…CB2 receptors, however, are primarily found on immune cells and in peripheral tissues that interact with Gαi proteins to modulate various immune responses and inflammatory processes 27,28 . It is reported that the activation of CB2 receptors is also capable of inhibiting adenylyl cyclase activity, reducing cAMP levels, but leading to a decrease in protein kinase A (PKA) activation, contributing to the dampening of immune cell activation and cytokine release 29 .…”
Section: Cannabinoid Receptors and Periodontitismentioning
confidence: 99%
“…cAMP assays were performed using the CAMYEL BRET-based biosensor (ATCC MBA-277) with methodology similar to that published previously (Sharma et al, 2023;Singh et al, 2019). Cells were prepared and transfected as for receptor and accessory protein detection, except that cells were seeded into PDL-treated white plates (Corning, Corning, NY, USA), and the CAMYEL plasmid (7 fmol per well; 23.8 ng per well) was co-transfected.…”
Section: Camp Assaymentioning
confidence: 99%
“…Further to our earlier study (Finlay et al, 2016), we undertook pilot experiments for dissociation of Gα i3 from β 3 γ 9 (TRUPATH; n = 1) and plasma membrane translocation of hβ-arrestin-2 (bystander BRET method described in Ibsen et al, 2019;Sharma et al, 2023;n = 2).…”
Section: Cannabinoid Receptor Signalling With and Without Mrap Co-exp...mentioning
confidence: 99%